(untitled) (Revista de Ciências Agroveterinárias, 2020)
The brazilian rice market prioritizes the consumption of polished white rice. However, there are demands for special types. The estimation of genetic divergence is important for genetic improvement, as it allows the selection of parents in controlled crossbreeding systems. Thus, the objectives of this work were to indicate the relative contribution of the evaluated traits to the genetic dissimilarity and to evaluate the genetic divergence among genotypes of special types of rice by two different methods of grouping. The experiment was carried out from October 2012 to March 2013, at the UFRRJ, Seropédica, RJ. The design used was in randomized blocks, with five replications. The treatments consisted of the genotypes Caiapó, Vermelho Pequeno, IAC 300, IAC 400 and IAC 500. The measure of dissimilarity adopted was the Euclidean distance. Two different optimization methods were used: the Tocher optimization method and the UPGMA (Unweighted Pair-Group Method using Arithmetic Averages) hierarchical method. The genotypes Caiapó and Vermelho Pequeno were in different heterotic groups in relation to the genotypes IAC 300 and IAC 400, using the clustering method used. It was found that the yield trait was the one that most influenced the total variation.